Penelitian Fenomenologi Model Gaya Kepemimpinan Badan Eksekutif Mahasiswa dan Dewan Mahasiswa Fakultas - Mochamad Ilham Bismo (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2020)
This research was conducted to determine the leadership style model found in the Student Executive Board (Badan Eksekutif Mahasiswa/BEM) and Student Council of the Faculty of Psychology, State University of Malang (Dewan Mahasiswa Fakultas/DMF). The analysis used in this study is a phenomenological model using triangulation techniques to validate the data. The participants in the study amounted to 2 people, as the main participants. The results showed that the head of BEM and the head of DMF had a transformational and transactional leadership style model. The head of BEM is quite visible with prominent aspects, namely the orientation of human relations, task orientation, and goal orientation; while the DMF chairman is quite visible in transactional and transformational leadership styles.